Gentianella viridiflora (Gentianaceae), a new species from the Peruvian Andes - Pfanzelt, Simon; Sylvester, Steven; Ammann, Lolita; Sylvester, Mitsy (Phytotaxa, 2015)
Gentianella viridiflora (Gentianaceae, Gentianeae, Swertiinae), here described and illustrated, is a new species from the Cordillera Vilcabamba, southern Peru. Its yellowish-green corolla distinguishes it from other South American species of the genus that share a similar set of morphological features. The new species is known only from the type locality where it occurs in grazed areas next to Polylepis woodland.